Unsedated Transnasal Endoscopy: A Canadian Experience in Daily Practice - Sarah Cho; Naveen Arya; Katherine Swan; Maria Cirocco; Gabor Kandel; Paul Kortan; Norman Marcon (Canadian Journal of Gastroenterology)
BACKGROUND: Esophagogastroduodenoscopy (EGD) is the most frequently performed diagnostic procedure for upper gastrointestinal disorders. The procedure is routinely performed under conscious sedation in North America. A significant proportion of morbidity and mortality associated with EGD is related to hypoxia due to conscious sedation. The use of sedation is also associated with an increase in cost, loss of work on the day of endoscopy and the need for the patient to be accompanied home after the procedure. Transnasal endoscopy has advantages such as no sedation and less patient monitoring, nursing time and expenses than conventional per oral EGD.